KARAKTERISTIK BUDAYA ORGANISASI, KEMAMPUAN ADAPTASI, DAN KINERJA USAHA MIKRO KECIL MENENGAH - Hyginus Suseno Triyanto Widodo; Aloysius Triwanggono (Fakultas Ekonomi, Universitas Sanata Dharma Yogyakarta, 2018)
This research aimed to find strength of corporate culture characteristics, adapt culture, and performance of small and medium industries. This study involved 40 respondents of small and medium industries owner located in Melikan Klaten Jawa Tengah and Krebet Bantul Daerah Istimewa Yogyakarta. This research is conducted using a descriptive analysis and non-parametric correlation. The findings showed that 42,8 percent of small and medium industry owners were categorized in strong and very strong corporate culture, 47,5 percent possess a good adapt culture, and 50 percent of respondent admitted that they have higher performance . The other result showed significants correlation between corporate culture, adapt culture, and performances.